Pengaruh Profitabilitas dan Opini Audit Tahun Sebelumnya terhadap Opini Audit Going Concern (Studi Empiris pada Perusahaan Manufaktur yang Terdaftar di Bursa Efek Indonesia Tahun 2011-2014) - Kharina Windi Yohana Sari; Endang Ruhiyat (Jurnal Ilmiah Akuntansi Universitas Pamulang, 2016)
This study aims to obtain empirical evidence about the effect of profitability on a going concern audit opinion, the effect of prior year's audit opinion on going concern audit opinion, as well as the simultaneous influence profitability and prior year's audit opinion on going concern audit opinion. Measurement indicators of profitability is return on assets, whereas the previous year's audit opinion and going concern audit opinion is measured by a dummy variable. The sample in this research are 21 companies listed on the Stock Exchange during the fourth period of the study (2011-2014) thus obtained samples of data representing 84 years of research. The research data in the form of financial statements audited by independent auditors obtained from the official website of the Stock Exchange www.idx.com. Sampling method used is purposive sampling method of obtaining samples based on certain criteria. Hypothesis testing is done by using logistic regression analysis of the data for the dependent variable and one independent variable in the study is a dichotomy. The data collected, then processed using an application program SPSS 22.0 for Windows. Based on the results of testing the hypothesis of the obtained evidence that profitability has no significant negative effect on going concern audit opinion, while the previous year's audit opinion in a positive significant effect on the going concern audit opinion. Simultaneous hypothesis testing showed that the profitability and the prior year's audit opinion is jointly significant effect tehadap going concern audit opinion.